IMPLEMENTASI PENDIDIKAN INKLUSI PADA ANAK USIA DINI (STUDI PADA PAUD INKLUSI DI KABUPATEN KEBUMEN) - lilis madyawati (INSANIA : Jurnal Pemikiran Alternatif Kependidikan, 2020)
Abstract This study aims at describing the implementation of inclusive early childhood education in inclusive preschools in Kebumen Regency Central Java as the effort to provide proper services to the children with special needs. It was done in three inclusive preschools in Kebumen to get data on the appropriateness of the implementation of the inclusion and the services to the children with special needs. It was a qualitative research applying interview with the teachers, staffs, and parents as the data collection method. An observation was also conducted to directly observe the playing and teaching learning activities. Document analysis was also employed to obtain supporting data related to the implementation of the inclusion. The result showed that the inclusive preschools in Kebumen have tried to implement the regular curriculum though there were separated treatment for the children with special needs from the limited human resources who mostly do not fit the children’s special needs. Keywords: inclusive education, early childhood.